Meningkatkan Keterampilan Membuat Sulam Kalocsa Melalui Model Pembelajaran Direct Instruction Bagi Anak Tunarungu - Kuntum Khoiroh Ummah; Zulmiyetri Zulmiyetri (Universitas Negeri Padang, 2020)
This paper describes the problem of two students who experience problems in learning skills to make kalocsa embroidery. Observations show that children have good interests and talents in embroidery. But the ability of children is minimal in making Kalocsa embroidery neatly. One way to overcome this is to teach making kalocsa embroidery through classroom action research methods. Through training, making Kalocsa embroidery gives children the opportunity to practice independently step by step in a structured manner so that it helps children to understand it more easily. Direct instruction learning model can improve the skills to make kalocsa embroidery